1129 UK Based Experience of The Elipsetm Intragastric Balloon; Short Term Safety and Effectiveness. (12th October 2021) - Sandhya, A; Oyewole, B; Stefanova, I; Mangat, S; Monkhouse, S
Abstract: Aim: Intra Gastric Balloons (IGB) have been used over the last three decades as a minimally invasive, non-surgical weight-loss option. The ElipseTM gastric balloon (EIGB) is a 'procedure-less' gastric balloon which can be placed in an average of 20 minutes without the need of endoscopy or sedation. The aim of our study is to investigate the first cohort of patients in uk who underwent IGB capsule and short term follow up. Method: Single centre retrospective study of the first consecutive 202 patients that had the Eclipse IGB inserted between May 2018 and November 2020. Patients swallow the Elipse TM capsule and pre-inflation x-ray is taken to confirm correct positioning after which the gastric balloon is inflated with 550mls of sterile water and a post-inflation x-ray is taken. The balloon is designed to be in-situ for 4 months and then automatically deflates. Results: Out of 202 patients 24 were lost to follow-up, 146 patients followed up to an average of 15 weeks, while 26 patients followed up to 4 weeks. Average weight loss at 4 weeks was 6% Total Weight Loss (%TWL) while at last follow up 9.63% TWL. Majority of patients experienced post procedural reflux, abdominal pain, bloating and vomiting. 6 patients had early removal of the balloon due to severe symptoms (4), pancreatitis (1) and hyperinflation (1). 1 had early expulsion at 2 months. Conclusions: Eclipse IGB is safe and effective in selective patients, however long-term follow is needed to compare it with the other balloons in terms of significant and sustained weight loss.